2012
DOI: 10.4049/jimmunol.1102190
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Epitope-Specific Naive CD4+ T Cells Correlates with Immunodominance in the Human Memory Repertoire

Abstract: The frequency of epitope specific naïve CD4+ T cells in humans has not been extensively examined. In this study, a systematic approach was used to examine the frequency of CD4+ T cells that recognize the Protective Antigen of Bacillus anthracis in both Anthrax Vaccine Adsorbed vaccinees and non-vaccinees with HLA-DRB1*01:01 haplotypes. Three epitopes were identified that had distinct degrees of immunodominance in subjects that had received the vaccine. Average naïve precursor frequencies of T cells specific fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
123
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 44 publications
11
123
0
Order By: Relevance
“…Accordingly, the size of the naive CD4 T cell repertoire from various T cell epitopes investigated in mice has been found to range from 0.8 to 15 cells per million (41,42) and was correlated with the amplitude of the T cell response (42). More recently, analysis of the CD4 T cell repertoire of HLA-DRB*0101-restricted T cell epitopes of protective Ags of Bacillus anthracis before and after vaccination showed that the frequencies of epitope-specific memory CD4 + T cells in vaccinees were directly correlated with the frequencies of precursors in the naive repertoire (43). Our data therefore extend these observations to promiscuous HIV-specific CD4 T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the size of the naive CD4 T cell repertoire from various T cell epitopes investigated in mice has been found to range from 0.8 to 15 cells per million (41,42) and was correlated with the amplitude of the T cell response (42). More recently, analysis of the CD4 T cell repertoire of HLA-DRB*0101-restricted T cell epitopes of protective Ags of Bacillus anthracis before and after vaccination showed that the frequencies of epitope-specific memory CD4 + T cells in vaccinees were directly correlated with the frequencies of precursors in the naive repertoire (43). Our data therefore extend these observations to promiscuous HIV-specific CD4 T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…A low level of MDK is detected in normal subjects (44), and this residual expression may contribute to reduce the MDK T cell repertoire. According to others (45,46), injection of recombinant MDK is expected to induce a CD4 ϩ T cell response in humans beings with a limited amplitude and consequently be poorly immunogenic (42,43,47). This could be an advantage for therapeutic applications of the MDK protein to treat cardiac ischemia (48) and neuronal disorders (49).…”
Section: Discussionmentioning
confidence: 99%
“…In other antigenic systems, this discrepancy has been found to be related to the number of pre-existing CD4 T lymphocytes. In mice, the size of the naive CD4 T cell repertoire from various T cell epitopes was correlated with the amplitude of the T cell response (18), whereas in humans the frequencies of epitope-specific memory CD4 T cells in vaccinees were directly correlated with the frequencies of precursors in the naive repertoire (19,20). In fact, little work has been done in multiple donors on the size of the repertoire of CD4 T cells specific for epitopes identified in tumor Ags (16,17,21).…”
mentioning
confidence: 99%